Design for a highly anti-interference He-Ne laser with novel multi-layer weakly coupled heat dissipation structure. (December 2022) - Yang, Hongxing; Yin, Ziqi; Wang, Xinyue; Hu, Pengcheng; Yang, Ruitao; Fu, Haijin; xing, Xu; Tan, Jiubin
Highlights: A novel multi-layer weakly coupled heat dissipation structure. The temperature distribution of traditional strongly coupled heat dissipation structure is nonuniform. Weakly coupled layer improves the anti-interference ability of the laser. Abstract: A novel multi-layer weakly coupled heat dissipation structure (MWHDS) with a low thermal conductivity layer between the metal layer and the thin-film heater of the laser is proposed. To reduce the influence of large temperature drift on high-precision frequency stabilisation, the anti-interference ability of the traditional strongly coupled water-cooling heat dissipation structure (SWHDS) is analyzed. Comparative simulation results of the aforementioned structures demonstrated that MWHDS has a better anti-interference ability than that of SWHDS. The experiments indicated that the laser with an MWHDS can resist the fluctuations in ambient temperature ( 15 ° C - 32 ° C ) and the water temperature ( 19 . 5 ° C - 24 . 5 ° C ), respectively, whose frequency stability according to the Allan variance is 2.1 × 10 - 11 ( τ = 10 s).